Severe falciparum and vivax malaria on the Thailand-Myanmar border: a review of 1503 cases - Chu, CS; Stolbrink, M; Stolady, D; Saito, M; Beau, C; Choun, K; Wah, TG; Mu, N; Htoo, K; Nu, B; Keereevijit, A; Wiladpaingern, J; et al. (Oxford University Press, 2023)
Background: The northwestern border of Thailand is an area of low seasonal malaria transmission. Until recent successful malaria elimination activities, malaria was a major cause of disease and death. Historically the incidences of symptomatic Plasmodium falciparum and Plasmodium vivax malaria were approximately similar. Methods: All malaria cases managed in the Shoklo Malaria Research Unit along the Thailand-Myanmar border between 2000 and 2016 were reviewed. Results: There were 80 841 consultations for symptomatic P. vivax and 94 467 for symptomatic P. falciparum malaria. Overall, 4844 (5.1%) patients with P. falciparum malaria were admitted to field hospitals, of whom 66 died, compared with 278 (0.34%) with P. vivax malaria, of whom 4 died (3 had diagnoses of sepsis, so the contribution of malaria to their fatal outcomes is uncertain). Applying the 2015 World Health Organization severe malaria criteria, 68 of 80 841 P. vivax admissions (0.08%) and 1482 of 94 467 P. falciparum admissions (1.6%) were classified as severe. Overall, patients with P. falciparum malaria were 15 (95% confidence interval, 13.2–16.8) times more likely than those with P. vivax malaria to require hospital admission, 19 (14.6–23.8) times more likely to develop severe malaria, and ≥14 (5.1–38.7) times more likely to die. Conclusions: In this area, both P. falciparum and P. vivax infections were important causes of hospitalization, but life-threatening P. vivax illness was rare.